Methylphenidate and Modafinil: egalitarian justice and policies of access to pharmacological cognitive enhancement - Loewe, Daniel (Acta Bioethica, 2017)
The article addresses criteria for access to pharmacological cognitive enhancement technologies, especially modafinil and methylphenidate, to healthy adults. From the perspective of equalitarian justice and taking as point of reference Rawls’ theory of justice it argues in favor of a policy of open market access, but facilitated for the worst-off.